A novel revolute joint of variable stiffness with reconfigurability. (March 2019) - Li, Zhongyi; Bai, Shaoping
Highlights: A novel joint mechanism of variable stiffness with reconfigurability is proposed. The new joint can be easily reconfigured by change of cable wrapping pattern to increase the stiffness. The stiffness of the joint can vary in different modes including linear, hardening, and softening modes. Mathematical stiffness model of the joint is duly developed. Experiment results with a prototype validate the ability of stiffness adjustment of the new joint mechanism. Abstract: In this paper, a novel revolute joint of variable stiffness with reconfigurability (JVSR) is presented. The JVSR is designed with a compliant joint mechanism, and is able to vary widely its stiffness in multiple modes, namely, linear, hardening and softening modes. This brings the joint for many potential applications in novel transmission and robotics. In the paper, mathematical models of joint stiffness are developed for the JVSR, with which influences of design parameters are analyzed. A prototype of JVSR is constructed and preliminary test results validate the model. A design case is included to illustrate the application of the JVSR in exoskeletons.